Education 4.0 Dari Industry 4.0 dan Adaptasinya di New Normal dalam Webinar Series LPKHA UNHAR Medan - Tommy Tommy; Imran Lubis; Rosyidah Siregar; Ruswan Nurmadi; Andi Marwan Elhanafi (Universitas Harapan Medan, 2021)
The industrial revolution 4.0 is marked by competitive competition and rapid information in all sectors, including human resources. Indonesia is required to have strong competitiveness in order to be able to align itself with other countries. Advances in Information and Communication Technology and the era of the industrial revolution 4.0 must be balanced with a supportive educational curriculum so as to produce Human Resources (HR) who have competence and are able to compete. Curriculum policies must collaborate with students' abilities in the pedagogical dimensions, life skills, the ability to live together (collaboration), critical thinking, and creativity. Students must have soft skills, transversal skills, life skills, and skills that are not directly related to certain work and academic fields.